The Diversity and Shared Culture of Lusheng in Guangxi: An Interethnic Symbol in Southwest China - Zhuo, Chu (Postgraduate Program of Institut Seni Budaya Indonesia Bandung, 2025)
The lusheng, a traditional Chinese bamboo wind instrument, is predominantly located in southwestern China, where ethnic minorities reside. In Guangxi, this instrument has assumed several shapes. For instance, Sanjiang possesses a six-pipe lusheng, Rongshui features a fifteen-pipe variant, and Longlin showcases enormous examples measuring six meters in height. Collectively, these encompass over 10 distinct varieties, with heights varying from 30 cm to 6 meters. The lusheng has historically evolved beyond its musical purpose to serve as a spiritual emblem for the Dong, Miao, Yao, and other ethnic communities. During events like as the Miao New Year, Slope Meetings, and the Pan Wang Festival, its booming tones reverberate through communities, functioning as ceremonial fanfares and repositories of collective memory. The performance system demonstrates extensive dimensionality. Solo compositions such as